Impact of cooking on the sensory perception and volatile compounds of Takifugu rubripes. (1st March 2022) - Zhang, Danni; Yang, Ni; Fisk, Ian D.; Li, Jintao; Liu, Yuan; Wang, Wenli
Highlights: Twenty-two sensory descriptors were developed for cooked T. rubripes . Cooked T. rubripes could be differentiated by orthonasal aroma and mouthfeel. Roasting process was the adapted method to reduce off-notes of cooked T. rubripes . Off-notes of cooked T. rubripes highly correlated with most aldehydes and alcohols. Mouthfeel highly associated with water properties of cooked T. rubripes . Abstract: Takifugu rubripes is well-known for its unique flavour but can also develop a putrid off-note. To eliminate off-note and promote desirable flavour, four cooking processes (boiling, steaming, microwave-heating and roasting) were explored to determine their effects on cooked T. rubripes . The temperature and water dynamics, physico-chemical properties were analysed and correlated with sensory qualities. The changes of centre temperature dynamics during cooking decreased the water mobility and led to varied sensory properties. Six out of ten orthonasal aroma attributes and four out of five mouthfeel attributes were significantly different among samples ( p < 0.05). Based on partial least squares regression analysis, orthonasal aroma attributes "roasted" and "earthy/putrid fish" highly correlated with the volatile compounds generated from Maillard reaction and lipid oxidation, respectively; meanwhile mouthfeel attributes of chewy/fibre and tender/juicy were highly associated with water loss and moisture, respectively. This study provides insights for optimising cooking conditions to create desirable fish flavour.